Clinical Efficacy of Domestic Preparation of Ursodeoxycholic Acid in Comprehensive Treatment of Hyperbilirubinemia in Premature Infants - D.O. Dobryansky; L.V. Bonetska; I.O. Nosova; K.V. Orel; T.V. Telyegina; O.V. Bezpalko; Yu.Yu. Dubrovna; S.V. Protsyk; O.Ya. Detsik (Zaslavsky O.Yu., 2014)
Several small pilot clinical studies suggest that the use of ursodeoxycholic acid (UDCA) may facilitate the course of neonatal jaundice. The aim of the work was to evaluate the clinical efficacy of Ukrliv® suspension in comprehensive treatment of hyperbilirubinemia in premature infants. In an open randomized study there were enrolled 35 preterm infants (19 - in the study, 16 - in the control group). Inclusion criteria were premature birth and hyperbilirubinemia (total serum bilirubin levels > 225 mmol/l) in the early neonatal period. Newborns in the study group, in addition to phototherapy, received Ukrliv® suspension in a daily dose of 20 mg/kg for 14 days. Formed groups did not differ in the main clinical characteristics and baseline concentrations of serum bilirubin. Children in both groups had a significant reduction in the initial concentrations of total serum bilirubin. During the first 3 days of treatment related dynamics was 44% in the study group versus 32% in the control one, ensuring the achievement of significant differences between the groups in the level of total and direct bilirubin at the time of completion of UDCA course. In infants from the study group jaundice was less prolonged. The drug was well tolerated by infants, no adverse effects of its use were revealed. Thus, the obtained results allow us to draw conclusions about the appropriateness of Ukrliv® suspension administration in comprehensive treatment of premature infants with hyperbilirubinemia.